1974
DOI: 10.1073/pnas.71.9.3350
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Actions of Neuroactive Drugs by Changing Brain Protein Synthesis

Abstract: Diminution of cerebral protein synthesis diminished the cerebral responses of mice to some neuroactive drugs, while an increase in synthesis increased the responses. Protein synthesis in whole brains (tested in vitro ) was diminished by giving living mice different inhibitors by different routes. The inhibitors tested (chloramphenicol, cycloheximide, and puromycin) diminished the behavioral responses of the mice to levodopa without affecting either its cerebral uptake or its conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is plausible that the neurochemical consequences of these lesions were responsible for the altered immune status observed. Indeed, depletion of storage pool DA and NE by reserpine produced immunosuppression (Dukor et al, 1966); stimulating DA receptors appeared to enhance immune functioning Tang, Cotzias, & Dunn, 1974).…”
Section: Neurochemical Hormonal and Immunological Interactionsmentioning
confidence: 99%
“…It is plausible that the neurochemical consequences of these lesions were responsible for the altered immune status observed. Indeed, depletion of storage pool DA and NE by reserpine produced immunosuppression (Dukor et al, 1966); stimulating DA receptors appeared to enhance immune functioning Tang, Cotzias, & Dunn, 1974).…”
Section: Neurochemical Hormonal and Immunological Interactionsmentioning
confidence: 99%
“…(V-Methyl-DA, a compound that showed no dopaminergic activity in mice (50-150 pg/g) and only a weak one in nigral-lesioned rats at lethal dosages (25 pg/g), stimulated cAMP as much as did DA under the same conditions. In contrast, 22 showed no dopaminergic effects in any of these tests.…”
Section: Scheme I Scheme Iimentioning
confidence: 60%
“…After synthesizing a series of 1,2,3,4tetrahydroisoquinolines (19a-c) and piperidines we found that some of the former had central cholinergic activities. To preserve dopaminergic while eliminating cholinergic activity we synthesized and investigated N,Ndialkyl-substituted dopamines (DA) (9,(22)(23)(24)(25). When we found that three relatively nontoxic alkyl-substituted DA had dopaminergic activity in lesioned mice and rats, we deemed them worthy of testing on DA-activated adenylate cyclase in homogenized mouse caudate nuclei6•7 to confirm this activity.…”
mentioning
confidence: 99%